Electronically Divergent Triscyclometalated Iridium(III) 2-(1-naphthyl)pyridine Complexes and Their Application in Three-Component Methoxytrifluoromethylation of Styrene - Njogu, Rachael E.N.; Fodran, Peter; Tian, Yuxi; Njenga, Lydia W.; Kariuki, David K.; Yusuf, Amir O.; Scheblykin, Ivan; Wendt, Ola F.; Wallentin, Carl-Johan (Synlett, 2019)
A systematic study of the photophysical and electrochemical properties of triscyclometalated homoleptic iridium(III) complexes based on 2-(1-naphthyl)pyridine (npy) ligands is presented. A systematic investigation of ligand substitution patterns showed an influence on the lifetime of the excited state, with slight changes in the absorption and emission spectral features. Specifically, the emission lifetime of a complex of an npy ligand substituted with a strongly electron-withdrawing trifluoromethyl group was longer than that of the corresponding complex with the electronically nonperturbed ligand (3.7 μs versus 1.5 μs). Electronically complementary ligands and complexes with orthogonal configurations showed slightly shorter excited state lifetimes compared with unsubstituted npy (1.4–3.0 μs). All complexes displayed reversible or quasireversible redox-couple processes, with the complex of the trifluoromethylated ligand showing the highest ground-state oxidation potential E1/2ox [Ir(III)/Ir(IV) = 0.95 V vs. SCE in CH2Cl2]. This study showed that these complexes can be used as efficient photoredox catalysts, as demonstrated by their application in a regioselective methoxytrifluoromethylation in which the npy complexes showed equal or better performance compared with the archetypical photoredox catalyst tris[2-phenylpyridinato]iridium(III).
Keywords: photoredox catalysis; iridium catalysis; oxytrifluoromethylation; styrene; naphthylpyridines; ligands